Effect of a sustained reduction in plasma free fatty acid concentration on insulin signalling and inflammation in skeletal muscle from human subjects. (3rd May 2013) - Liang, Hanyu; Tantiwong, Puntip; Sriwijitkamol, Apiradee; Shanmugasundaram, Karthigayan; Mohan, Sumathy; Espinoza, Sara; DeFronzo, Ralph A.; Dubé, John J.; Musi, Nicolas
Key points Reducing free fatty acids in the circulation gives protection against muscle insulin resistance. In the present study, we investigated the mechanism by which free fatty acid reduction improves muscle insulin sensitivity. The antilipolytic drug acipimox reduced the plasma concentration of unsaturated and saturated fatty acids in insulin‐resistant (obese and type 2 diabetic) subjects. The reduction in plasma free fatty acid concentration caused by acipimox led to an improvement in local inflammation and insulin signalling in skeletal muscle. The improvements in local inflammation and insulin signalling were more pronounced in obese type 2 diabetic subjects than obese non‐diabetic individuals, suggesting that diabetic subjects are more susceptible to the toxic effect of circulating free fatty acids. Abstract Free fatty acids (FFAs) have been implicated in the pathogenesis of insulin resistance. Reducing plasma FFA concentration in obese and type 2 diabetic (T2DM) subjects improves insulin sensitivity. However, the molecular mechanism by which FFA reduction improves insulin sensitivity in human subjects is not fully understood. In the present study, we tested the hypothesis that pharmacological FFA reduction enhances insulin action by reducing local (muscle) inflammation, leading to improved insulin signalling. Insulin‐stimulated total glucose disposal (TGD), plasma FFA species, muscle insulin signalling, IκBα protein, c‐Jun phosphorylation, inflammatory gene (toll‐like receptor 4 and monocyte chemotactic protein 1) expression, and ceramide and diacylglycerol (DAG) content were measured in muscle from a group of obese and T2DM subjects before and after administration of the antilipolytic drug acipimox for 7 days, and the results were compared to lean individuals. We found that obese and T2DM subjects had elevated saturated and unsaturated FFAs in plasma, and acipimox reduced all FFA species. Acipimox‐induced reductions in plasma FFAs improved TGD and insulin signalling in obese and T2DM subjects. Acipimox increased IκBα protein (an indication of decreased IκB kinase–nuclear factor κB signalling) in both obese and T2DM subjects, but did not affect c‐Jun phosphorylation in any group. Acipimox also decreased inflammatory gene expression, although this reduction only occurred in T2DM subjects. Ceramide and DAG content did not change. To summarize, pharmacological FFA reduction improves insulin signalling in muscle from insulin‐resistant subjects. This beneficial effect on insulin action could be related to a decrease in local inflammation. Notably, the improvements in insulin action were more pronounced in T2DM, indicating that these subjects are more susceptible to the toxic effect of FFAs.